2023
DOI: 10.1007/s13399-023-03967-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring HTL pathways in carbohydrate–protein mixture: a study on glucose–glycine interaction

Abstract: The hydrothermal liquefaction (HTL) of biomass is a strategic process to convert wet and waste feedstocks into liquid biofuel. In this work, we investigated the hydrothermal liquefaction of glucose and glycine, alone and together, to mimic the composition of low-lipid content biomass. Experimental tests were performed in a batch setup in the temperature range of 200–350 °C. As the feeding composition and temperature changed, the distribution among the different phases (gas, solid, biocrude, and aqueous phase) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Contextually, several experimental and modelling studies based on model compounds have been reported in the literature to gain deeper knowledge on the influence of biomass macro-components on the yield and quality of bio-crude (and, consequently, on the prevailing reaction pathways), also highlighting the possible synergistic or antagonistic effects [39][40][41][42]. Chacón-Parra et al [40] investigated Maillard reactions during HTL by adopting a central composite design to validate the impact of the carbohydrate/protein mass ratio on the process performance at different temperature and residence time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contextually, several experimental and modelling studies based on model compounds have been reported in the literature to gain deeper knowledge on the influence of biomass macro-components on the yield and quality of bio-crude (and, consequently, on the prevailing reaction pathways), also highlighting the possible synergistic or antagonistic effects [39][40][41][42]. Chacón-Parra et al [40] investigated Maillard reactions during HTL by adopting a central composite design to validate the impact of the carbohydrate/protein mass ratio on the process performance at different temperature and residence time.…”
Section: Introductionmentioning
confidence: 99%
“…Their work showed that a protein-to-carbohydrate mass ratio of 2:1 is likely to maximise the volatile fraction, the elemental carbon and the higher heating value (HHV) of the bio-crude, with a maximum yield of 90−95%. In the work of Tito et al [41], the interaction between carbohydrates and proteins during hydrothermal liquefaction at different temperatures was studied, with experimental tests carried out with glucose and glycine as model compounds. This study reinforced the hypothesis that carbohydrates and proteins have a strong interaction during HTL, highlighting the central role of temperature in the regulation of this interaction.…”
Section: Introductionmentioning
confidence: 99%